Bolívar, Trujillo and the makeup upon the final battles, 1823-1824 - Alvarado Luna, Patricio A. (2024)
The years between 1822 and 1823 are characterized by political instability and military mistakes by the authorities of independent Peru. This situation was different for the royalist forces in the southern Andes, who even managed to undertake various raids on Lima. Bolívar’s arrival in Peru sought to transform this situation; however, he faced a series of challenges and intrigues. This work analyzes, focusing on epistolary documentation, newspapers, and memoirs, the measures taken by Simón Bolívar in northern Peru with a view to the development of the military campaigns in 1824. It explains and analyzes why Bolívar left Lima for northern Peru, settling in the city of Trujillo. Additionally, the logistical and military situation of the independence and royalist forces in the first months of 1824 is compared. Finally, the internal and external reasons that led to the development of the battles of Junín and Ayacucho are examined.